PERAN KEDUA ORANG TUA DAN KELUARGA (Tinjuan Psikologi Perkembangan Islam dalam Membentuk Kepribadian Anak) - Syafi’ ah Syafi’ ah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Families with any community is a group of social ties in the life of a family household. Both parents, especially fathers as heads of households and mothers as heads of households, the main actors in the coloring process of coaching, education, and petumbuhan and mental development of children's personality. Personal or ideal personality of children who are expected to rely heavily on the efforts of both parents as early as possible so that children can understand the various introductions, social experiences through a series of exercises guidance and education, particularly through the introduction, development and religious spiritual education as well. With through a variety of educationinstruction, accompanied by a spiritual moral spirit, is a guarantee that children will be no hope